2019
DOI: 10.1103/physrevd.100.056008
|View full text |Cite
|
Sign up to set email alerts
|

Coupled K+Λ and K0Λ photo

Abstract: The new γn → K 0 Λ data obtained from the CLAS and MAMI collaborations are analyzed by employing an effective Lagrangian method. The constructed model can describe all available experimental data in both γp → K + Λ and γn → K 0 Λ channels, simultaneously. The background part of the model is built from the appropriate intermediate states involving the nucleon, kaon, and hyperon exchanges, whereas the resonance part is constructed from the consistent interaction Lagrangians and propagators. To check the performa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 95 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…Indeed nucleon resonances around 1890 MeV are not well understood, since most of the information in this energy region is extracted from the data on reactions producing KΛ and KΣ final states and different N * 's couple with a similar strength to these channels. For example, different descriptions have been brought forward for the peak present around 1900 MeV in the γp → K + Λ total cross sections [48][49][50][51][52]. Furthermore, different quark models [53][54][55][56] predict a different mass for the third S 11 state, with the values lying near 2 GeV.…”
Section: Table Imentioning
confidence: 99%
“…Indeed nucleon resonances around 1890 MeV are not well understood, since most of the information in this energy region is extracted from the data on reactions producing KΛ and KΣ final states and different N * 's couple with a similar strength to these channels. For example, different descriptions have been brought forward for the peak present around 1900 MeV in the γp → K + Λ total cross sections [48][49][50][51][52]. Furthermore, different quark models [53][54][55][56] predict a different mass for the third S 11 state, with the values lying near 2 GeV.…”
Section: Table Imentioning
confidence: 99%
“…[3]. Later partial wave investigations [4][5][6], however, concluded that the peak corresponds to the presence of a 3/2 + N * (1900) state. An alternative description for the same peak in the data is provided in Ref.…”
Section: Introductionmentioning
confidence: 99%